Safety, efficacy, and cost-effectiveness evaluation of systemic treatments for refractory colorectal cancer: a systematic review and modeling study - Mingye Zhao; Yunlin Jiang; Taihang Shao; Wenxi Tang (Health Economics Review)
Abstract Objectives To conduct pooled estimates and comparative evaluations of safety and efficacy, alongside cost-effectiveness and value-based pricing analyses, for systemic treatments recommended by the National Comprehensive Cancer Network in refractory colorectal cancer. Methods A comprehensive search for related randomized controlled trials was conducted on PubMed, EMBASE, the Cochrane Library, and ClinicalTrials.gov. Safety was evaluated by aggregating treatment-related adverse events (TRAEs) and performing Bayesian network meta-analysis (NMA) for indirect comparisons. Pooled survival estimates of overall survival (OS) and progression-free survival (PFS) were conducted to assess treatment efficacy. For NMA of OS and PFS, time-variant fractional polynomial models were employed as the primary analysis, with Cox proportional hazards models used for result validation. Economic evaluations were performed using partitioned survival models from the US public sector perspective. Clinical parameters were sourced from meta-analyses; cost parameters included drug treatment, follow-up and administration, end-of-life care, and adverse event management expenses, which were obtained from the Federal Supply Schedule, public databases or published literature. Utility values were sourced from the CORRECT trial. Price simulations were also conducted. Robustness of results was confirmed by sensitivity and scenario analyses Results We included nine studies comprising 3,978 patients and incorporating six treatments recommended by NCCN, including best supportive care (BSC), regorafenib, regorafenib dose optimization (REDo), trifluridine/tipiracil (TAS-102), TAS-102 with bevacizumab (TAS-BEV), and fruquintinib. Targeted treatments increased serious TRAEs and grade 3 + TRAEs compared to BSC. However, no significant safety differences were found among the targeted therapies. Regarding efficacy, REDo led in median OS, while fruquintinib led in median PFS. NMA indicated that TAS-BEV had the greatest PFS and OS survival benefit, followed by fruquintinib and REDo. Cost-effectiveness analysis favored BSC as the least expensive and the most cost-effective profile. TAS-BEV had the greatest effectiveness, with TAS-102 being the most cost-effective among targeted therapies. For cost-effectiveness against BSC, the price reductions of TAS-102, fruquintinib, REDoS, regorafenib, and TAS-BEV were 39%, 24%, 14%, 8%, and 7%, respectively. Conclusions Targeted therapies have comparable safety; TAS-BEV is highly effective, TAS-102 is the top cost-effective targeted therapy. Treatment choice should balance individual patient needs with safety, efficacy, and cost.